1985
DOI: 10.1128/mcb.5.10.2866
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 regulates human metallothionein gene expression.

Abstract: Incubation of cultured human cells with interleukin 1 leads to increased expression of the human metallothionein-IIA gene. Recently, metallothionein has been shown to be an efficient free radical scavenger, and induction by interleukin 1 may be part of a protective response to minimize damage by hydroxyl radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(53 citation statements)
references
References 33 publications
1
49
2
1
Order By: Relevance
“…As a variety of endogenous factors (e.g. glucocorticosteroids, ILs, IFNg, TNF-a) are involved in the induction of the synthesis of intracellular MT, one may suggest that this may lead to an overprotection of tumour cells against apoptosis, and, on the other hand, supporting the metastatic behaviour of the tumour (Karin et al, 1985;Karasawa et al, 1987;Nath et al, 1988;Schroeder and Cousins, 1990;Sato and Sasaki, 1992;Tsangaris and TzortzatouStathopoulou, 1998;Miles et al, 2000;Nishimura et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a variety of endogenous factors (e.g. glucocorticosteroids, ILs, IFNg, TNF-a) are involved in the induction of the synthesis of intracellular MT, one may suggest that this may lead to an overprotection of tumour cells against apoptosis, and, on the other hand, supporting the metastatic behaviour of the tumour (Karin et al, 1985;Karasawa et al, 1987;Nath et al, 1988;Schroeder and Cousins, 1990;Sato and Sasaki, 1992;Tsangaris and TzortzatouStathopoulou, 1998;Miles et al, 2000;Nishimura et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They can protect cells against UV-/ionic radiation (Hansen et al, 1997;Hanada et al, 1998;Reeve et al, 2000) as well as cytotoxic alkylating agents including chemotherapeutics (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Sunada et al, 2005), modulate oxygen free radicals and nitric oxide and inhibit apoptosis (Tsangaris and Tzortzatou-Stathopoulou, 1998). The synthesis of MT is induced by group II heavy metal ions as well as by endogenous factors such as glucocorticoids, cytokines (interleukin (IL)-1 or IL-6, interferon g (IFNg), tumour necrosis factor a (TNF-a)) or vitamin D 3 (Karin et al, 1985;Karasawa et al, 1987;Schroeder and Cousins, 1990;Sato and Sasaki, 1992;Nishimura et al, 2000). There is also some evidence that inflammatory stressors (e.g.…”
mentioning
confidence: 99%
“…MT gene expression is predominantly regulated at the level of transcription [5][6][7][8][9]. Though the mechanism of regulation is poorly understood, rapid induction occurs upon exposure to metals [5] and, in mammalian cells, to various circulating factors such as glucocorticoid hormones [6], ainterferon [7], and interleukin-1 and other mediators of the inflammatory response [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Though the mechanism of regulation is poorly understood, rapid induction occurs upon exposure to metals [5] and, in mammalian cells, to various circulating factors such as glucocorticoid hormones [6], ainterferon [7], and interleukin-1 and other mediators of the inflammatory response [8,9]. It has been suggested that a common pathway for MT induction involves protein kinase C (PKC) activation since MT levels increase in serum-starved cells after treatment with growth factors and TPA, agents which function in part through PKC activation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…(rC) and this probably reflects the fact that IL-1 is a weaker gene activator than interferon on epithelial and fibroblastic cells. This is the case for the metallothionein I1 gene which is also inducible by interferon but which is only weakly induced by IL-1 in some cell lines and not in others [16].…”
Section: Three Irs-like Sequences Are Present In the Ifi-56k Promotermentioning
confidence: 99%